Coding the assembly of polyoxotungstates with a programmable reaction system - Ruiz de la Oliva, Andreu; Sans, Victor; Miras, Haralampos N.; Long, De-Liang; Cronin, Leroy (American Chemical Society, 2017)
Chemical transformations are normally conducted in batch or flow mode, thereby allowing the chemistry to be temporally or spatially controlled, but these approaches are not normally combined dynamically. However, the investigation of the underlying chemistry masked by the self-assembly processes that often occur in one-pot reactions and exploitation of the potential of complex chemical systems requires control in both time and space. Additionally, maintaining the intermediate constituents of a self-assembled system “off equilibrium” and utilizing them dynamically at specific time intervals provide access to building blocks that cannot coexist under one-pot conditions and ultimately to the formation of new clusters. Herein, we implement the concept of a programmable networked reaction system, allowing us to connect discrete “one-pot” reactions that produce the building blockW11O38 ≡ W11 under different conditions and control, in real time, the assembly of a series of polyoxometalate clusters W12O42 ≡ W12, W22O74 ≡ W22 1a, W34O116 ≡ W34 2a, and W36O120 ≡ W36 3a, using pH and ultraviolet−visible monitoring. The programmable networked reaction system reveals that is possible to assemble a range of different clusters using W11-based building blocks, demonstrating the relationship between the clusters within the family of iso-polyoxotungstates, with the final structural motif being entirely dependent on the building block libraries generated in each separate reaction space within the network. In total, this approach led to the isolation of five distinct inorganic clusters using a “fixed” set of reagents and using a fully automated sequence code, rather than five entirely different reaction protocols. As such, this approach allows us to discover, record, and implement complex one-pot reaction syntheses in a more general way, increasing the yield and reproducibility and potentially giving access to nonspecialists.